2011
DOI: 10.1038/emboj.2011.253
|View full text |Cite
|
Sign up to set email alerts
|

ERK7 is a negative regulator of protein secretion in response to amino-acid starvation by modulating Sec16 membrane association

Abstract: RNAi screening for kinases regulating the functional organization of the early secretory pathway in Drosophila S2 cells has identified the atypical Mitotic-Associated Protein Kinase (MAPK) Extracellularly regulated kinase 7 (ERK7) as a new modulator. We found that ERK7 negatively regulates secretion in response to serum and amino-acid starvation, in both Drosophila and human cells. Under these conditions, ERK7 turnover through the proteasome is inhibited, and the resulting higher levels of this kinase lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
135
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(145 citation statements)
references
References 74 publications
6
135
0
Order By: Relevance
“…giERK2 lacks the extended C-terminal domain found in ERK7 and may not be regulated in the same manner, and yet in vitro kinase assays have shown that giERK2 is much more active than giERK1 (48). In other eukaryotes, ERK7 kinases have been shown to regulate protein secretion and cell proliferation (50,51). Our identification of an actin-ERK2 complex in Giardia and the localization of this kinase in the nucleus and throughout the cell do not exclude potentially conserved function.…”
Section: Discussionmentioning
confidence: 92%
“…giERK2 lacks the extended C-terminal domain found in ERK7 and may not be regulated in the same manner, and yet in vitro kinase assays have shown that giERK2 is much more active than giERK1 (48). In other eukaryotes, ERK7 kinases have been shown to regulate protein secretion and cell proliferation (50,51). Our identification of an actin-ERK2 complex in Giardia and the localization of this kinase in the nucleus and throughout the cell do not exclude potentially conserved function.…”
Section: Discussionmentioning
confidence: 92%
“…a strict COPII-dependent emergence of a secretory flux. Although this study focused the role of mitogens in regulating ERES, others have recently identified in Drosophila a novel response of ERES to amino acid starvation (Zacharogianni et al, 2014), which is distinct from the response to serum starvation reported previously (Zacharogianni et al, 2011). Amino acid starvation results in the formation of 'Sec bodies', where Sec16 and other COPII components are stored.…”
Section: Discussionmentioning
confidence: 97%
“…ERK7 undergoes autophosphorylation and is constitutively active 3 . Previous studies in cultured cells have shown that ERK7 is involved in the protection of genomic integrity, response to amino-acid starvation and autophagy [4][5][6] . However, its function in vivo remains largely unknown.…”
mentioning
confidence: 99%